New Zealand : 2010 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
New Zealand rode out the global crisis better than most advanced economies, thanks to strong demand from fast-growing Asian markets and the robust Australian economy, a flexible exchange rate, the absence of a banking crisis, and significant and effective policy easing. This 2010 Article IV Consultation highlights that a gradual recovery is expected to continue, with growth projected at 3 percent in 2010-11. The outlook is subject to downside risks related to the pace of global recovery and borrowing costs for countries with high external debt, such as New Zealand.